Evidence from comparative genomics for a complete sexual cycle in the "asexual" pathogenic yeast Candida glabrata - FARES, MARIO ALI; WOLFE, KENNETH (BioMed Central, 2003)
BACKGROUND: Candida glabrata is a pathogenic yeast of increasing medical concern. It has been regarded as asexual since it was first described in 1917, yet phylogenetic analyses have revealed that it is more closely related to sexual yeasts than other Candida species. We show here that the C. glabrata genome contains many genes apparently involved in sexual reproduction. RESULTS: By genome survey sequencing, we find that genes involved in mating and meiosis are as numerous in C. glabrata as in the sexual species Kluyveromyces delphensis, which is its closest known relative. C. glabrata has a putative mating-type (MAT) locus and a pheromone gene (MFALPHA2), as well as orthologs of at least 31 other Saccharomyces cerevisiae genes that have no known roles apart from mating or meiosis, including FUS3, IME1 and SMK1. CONCLUSIONS: We infer that C. glabrata is likely to have an undiscovered sexual stage in its life cycle, similar to that recently proposed for C. albicans. The two Candida species represent two distantly related yeast lineages that have independently become both pathogenic and 'asexual'. Parallel evolution in the two lineages as they adopted mammalian hosts resulted in separate but analogous switches from overtly sexual to cryptically sexual life cycles, possibly in response to defense by the host immune system.
PUBLISHED
Keywords: Genetics; Candida glabrata